Effectiveness of Investigator and Assistant Investigator Certification at the Special Criminal Investigation Directorate of Bengkulu Regional Police as a Mandatory Instrument to Improve Investigation Quality - Merawati, Andriyani; Anggoro, Purwadi Wahyu; Setiono, Joko (Greenation Publisher & Yayasan Global Resarch National, 2025)
This study examines the effectiveness of investigator and assistant investigator certifications at the Bengkulu Regional Police Criminal Investigation Unit as mandatory instruments for enhancing the quality of specialized criminal investigations. The certification process is outlined in Perpol No. 6 of 2019 and Perkap No. 99 of 2020, both of which emphasize the importance of competency standards and developing superior police human resources. The study analyzes how certification promotes legal compliance and enhances investigator professionalism through competency-based assessments. The research findings suggest that certified investigators have superior capabilities when conducting investigations by the Criminal Procedure Code (KUHAP) and Law No. 2 of 2002 by the National Police of the Republic of Indonesia. The improvement in investigation quality is reflected in investigations' completeness, accuracy, and compliance with legal procedures. This supports case success up to the P-21 stage. However, certification implementation faces obstacles such as limited trainers and competency assessors, an uneven distribution of certified investigators, and suboptimal integration of competency supervision between related work units. The study recommends strengthening internal regulations, digitizing training and competency assessments, and implementing an effective performance evaluation system to uniformly enhance investigator professionalism. These findings are expected to inform the development of human resource policies within the Indonesian National Police, promoting more professional and fair law enforcement.